Pengembangan Bahan Ajar Materi Aturan Pencacahan Menggunakan Pembelajaran Berbasis Masalah di SMA - Iis Juniati Lathiifah; Zulkardi Zulkardi; Somakim Somakim (Didaktik Matematika, 2015)
This study aims to produce teaching materials of enumeration rules were valid and practical based on the characteristics of problem-based learning and curriculum 2013 and to determine the potential effects of teaching materials on students ability to solve problems. The method used was the development of research which consists of two stages: a preliminary stage that includes the preparation and design then the formative stages of evaluation that includes self evaluation, expert reviews, one-to-one, small group, and a field test. The subjects were students of class XI MIA 6 SMAN 10 Palembang. Data collected by walkthrough, observation and tests. This research has produced teaching materials were valid and practical based on the characteristics of problem-based learning and curriculum 2013. Valid drawn from suggestions validator which states that teaching materials good based content in accordance with curriculum 2013, construct in accordance with the characteristics of problem-based learning and language according to the EYD, and have a potential effect on students ability to solve problems seen from the attitude, knowledge and skills in general was good and the results of the final evaluation test where the average student scores were categorized either.